The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5194/bg-12-1007-2015
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of phytoplankton aggregates and zooplankton fecal pellets to carbon export: insights from free-drifting sediment trap deployments in naturally iron-fertilised waters near the Kerguelen Plateau

Abstract: Abstract. The first KErguelen Ocean and Plateau compared Study (KEOPS1), conducted in the naturally iron-fertilised Kerguelen bloom, demonstrated that fecal material was the main pathway for exporting carbon to the deep ocean during summer (January-February 2005), suggesting a limited role of direct export via phytodetrital aggregates. The KEOPS2 project reinvestigated this issue during the spring bloom initiation (October-November 2011), when zooplankton communities may exert limited grazing pressure, and fur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
100
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 90 publications
26
100
2
Order By: Relevance
“…Only for one station (139), which evidenced a temporal decoupling between production and export (lowest Chl-a SW inventories and NPP rates), the export efficiency was 4 30% according to all techniques. Indeed, we found an inverse relationship between export efficiency and NPP (p o0.05; ST method: ρ¼ À0.95, n ¼8; SWST method: ρ¼ À0.89, n¼ 6) supporting recent observations (Cavan et al, 2015;Laurenceau-Cornec et al, 2015;Maiti et al, 2013). This relationship could be explained by a combination of temporal decoupling between primary production and export (Henson et al, 2015;Puigcorbé et al, 2017), and other processes such as zooplankton grazing (Cavan et al, 2015), bacterial activity and recycling efficiency (Maiti et al, 2013).…”
Section: Export Efficiencysupporting
confidence: 86%
See 1 more Smart Citation
“…Only for one station (139), which evidenced a temporal decoupling between production and export (lowest Chl-a SW inventories and NPP rates), the export efficiency was 4 30% according to all techniques. Indeed, we found an inverse relationship between export efficiency and NPP (p o0.05; ST method: ρ¼ À0.95, n ¼8; SWST method: ρ¼ À0.89, n¼ 6) supporting recent observations (Cavan et al, 2015;Laurenceau-Cornec et al, 2015;Maiti et al, 2013). This relationship could be explained by a combination of temporal decoupling between primary production and export (Henson et al, 2015;Puigcorbé et al, 2017), and other processes such as zooplankton grazing (Cavan et al, 2015), bacterial activity and recycling efficiency (Maiti et al, 2013).…”
Section: Export Efficiencysupporting
confidence: 86%
“…100-300 m below the euphotic zone depth, our understanding of the processes affecting sinking particles throughout this layer is still poor (Buesseler and Boyd, 2009). The vertical flux of organic matter throughout the water column is dominated by large particles such as marine snow and faecal pellets (Ebersbach et al, 2011;Fowler and Knauer, 1986;Laurenceau-Cornec et al, 2015) that can be attenuated to a large extent by zooplankton and microbial degradation (Giering et al, 2014;Iversen et al, 2010;Kiørbe, 2000;Smith et al, 1992). However, packaging of slowly sinking phytoplankton cells into large faecal pellets may play a key role in increasing the export and transfer efficiencies in the Southern Ocean (Cavan et al, 2015;Le Moigne et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The SAZ is more productive in the Atlantic sector and around 170 • W where iron concentrations are higher due to the proximity of land (Figure 2) (Comiso et al, 1993;de Baar et al, 1995;Moore and Abbott, 2000). Despite the low levels of primary productivity, export efficiency is high in HNLC waters of the SAZ, suggesting that small taxa contribute to a high proportion of carbon export (Trull et al, 2001b;Lam and Bishop, 2007;Cassar et al, 2015;Laurenceau-Cornec et al, 2015).…”
Section: Sub-antarctic Zonementioning
confidence: 99%
“…Note for example that at the complex R-2 reference station, a small export event held heavily silicified diatoms and that the material was efficiently remineralized in the upper mesopelagic layer as witnessed by the high MR values we observed for that station. For the KEOPS 2 A3 site, Laurenceau-Cornec et al (2015) reported that the sinking flux collected in the upper layer using gel-filled sediment traps was composed of phytodetrital aggregates that held slightly silicified diatoms . Even considering the shift from slightly to highly silicified material transfer between spring (KEOPS2) and summer (KEOPS 1), MR only slightly increases between both periods.…”
Section: Station A3 On the Plateaumentioning
confidence: 99%
“…The same area was visited earlier in 2005 during summer at a late stage of the bloom (KEOPS 1; January-February 2005), offering a unique opportunity to estimate the main carbon fluxes over most of the growth sea- son. Mesopelagic C remineralization estimates are compared to particle and biological parameters as reported in other papers included in this issue Christaki et al, 2014;Dehairs et al, 2014;Laurenceau-Cornec et al, 2015;Planchon et al, 2014;van der Merve et al, 2015) and in Blain et al (2007), Christaki et al (2008), Jacquet et al (2008a), Park et al (2008) and Savoye et al (2008).…”
Section: Introductionmentioning
confidence: 99%